METASTATIC MAMMARY GLAND CARCINOMA IN A GIANT OTTER (Pteronura brasiliensis) - Fujita, Estefani Segato (2024)
Diagnostics of neoplasia in otters kept in captivity have been discreetly increasing over the last years, especially in older individuals. Here, we describe a case of a mammary gland carcinoma in a nulliparous 17-year-old female giant otter (Pteronura brasiliensis) kept at the National Institute for Amazonian Research in Brazil. It represents the first report of mammary carcinoma in a giant otter. The animal presented with lameness of the right hind limb, weight loss, dyspnea, impaired locomotion, and signs of pain. Physical examination was performed with the observation of a medium sized mass of approximately 5 cm3 in the left mammary gland. On that occasion, samples for cytology and blood tests were collected. Results suggested the presence of mammary carcinoma and health alterations. The individual showed progressively poor health and was non-responsive to medical treatment. Euthanasia was performed and necropsy showed cachexia, a nodule in the mammary gland and an increase in the volume of mesenteric lymph nodes. Nodules from the mammary gland, pulmonary parenchyma, and mesenteric lymph node were collected for histopathological and immunohistochemistry analyses. Histopathology results revealed a mammary carcinoma complex subtype at stage II, with confirmed results by immunohistochemistry, which yielded positive results for CK Pan, CK19 and CK7 tumoral markers in the neoplastic cells. The regular health monitoring of captive otters may aid in the understanding of the prevalence and the etiology of this type of tumor, as also to take preventive measures to avoid premature death of individuals.